Synergism of a Novel 1,2,4-oxadiazole-containing Derivative with Oxacillin against Methicillin-Resistant Staphylococcus aureus - Elisabetta Buommino; Simona De Marino; Martina Sciarretta; Marialuisa Piccolo; Carmen Festa; Maria Valeria D'Auria (MDPI AG, 2021)
Staphylococcusaureus is an important opportunistic pathogen that causes many infections in humans and animals. The inappropriate use of antibiotics has favored the diffusion of methicillin-resistant S. aureus (MRSA), nullifying the efforts undertaken in the discovery of antimicrobial agents. Oxadiazole heterocycles represent privileged scaffolds for the development of new drugs because of their unique bioisosteric properties, easy synthesis, and therapeutic potential. A vast number of oxadiazole-containing derivatives have been discovered as potent antibacterial agents against multidrug-resistant MRSA strains. Here, we investigate the ability of a new library of oxadiazoles to contrast the growth of Gram-positive and Gram-negative strains. The strongest antimicrobial activity was obtained with compounds 3 (4 µM) and 12 (2 µM). Compound 12, selected for further evaluation, was found to be noncytotoxic on the HaCaT cell line up to 25 µM, bactericidal, and was able to improve the activity of oxacillin against the MRSA. The highest synergistic interaction was obtained with the combination values of 0.78 μM for compound 12, and 0.06 μg/mL for oxacillin. The FIC index value of 0.396 confirms the synergistic effect of compound 12 and oxacillin. MRSA treatment with compound 12 reduced the expression of genes included in the mec operon. In conclusion, 12 inhibited the growth of the MRSA and restored the activity of oxacillin, thus resulting in a promising compound in the treatment of MRSA infection.